Digital diffraction detection of protein markers for avian influenza. Issue 8 (16th March 2016) - Im, Hyungsoon; Park, Yong Il; Pathania, Divya; Castro, Cesar M.; Weissleder, Ralph; Lee, Hakho
Abstract : A smartphone-based assay is developed to detect soluble protein markers in point-of-care settings. Abstract : Rapid pathogen testing is expected to play a critical role in infection control and in limiting epidemics. Smartphones equipped with state-of-the-art computing and imaging technologies have emerged as new point-of-use (POU) sensing platforms. We herein report a new assay format for fast, sensitive and portable detection of avian influenza-associated antibodies.